Anti-fouling self-cleaning coating with micro-nano surface structure and preparation method of anti-fouling self-cleaning coating

By adding specific polymers and photocatalytic particles to the coating and curing them under ultraviolet light to form a micro-nano surface structure, the problem of the short-term anti-fouling effect of the existing superhydrophobic coating is solved, and a long-term self-cleaning effect is achieved.

CN119899583AActive Publication Date: 2025-04-29DONGZHOU CHEM IND (KUNSHAN) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411977773.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The anti-fouling effect of the existing superhydrophobic coating is relatively short-lived, and it is easy to cause the surface state to go from a non-wet Cassie-Baxter state to a completely wet Wenzel state, thereby losing superhydrophobic properties.

Method used

By adding aqueous polyurethane acrylate and photocatalytic degradation particles to the coating and curing under ultraviolet light, the surface of the coating is wrinkled and a micro-nano surface structure is formed to achieve a self-cleaning effect.

Benefits of technology

After the coating is cured with ultraviolet light, micro-nano structural wrinkles form on the surface, which significantly improves the anti-fouling performance and maintains a long-term self-cleaning effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220832510000011
    Figure BDA0005220832510000011
  • Figure BDA0005220832510000021
    Figure BDA0005220832510000021
  • Figure BDA0005220832510000051
    Figure BDA0005220832510000051
Patent Text Reader

Abstract

The invention provides an anti-fouling self-cleaning coating with a micro-nano surface structure. The anti-fouling self-cleaning coating comprises the following components: 25-35% of waterborne polyurethane acrylate, 10-20% of photocatalytic degradation particles, 1-2% of a dispersing agent, 1-2% of a defoaming agent, 3-5% of a UV photoinitiator, 0.4-1% of an adhesion promoter and the balance of water, wherein the water-based polyurethane acrylate is hard-chain polyurethane acrylate, the water-based polyurethane acrylate is coated in the photocatalytic degradation particles, and the water-based polyurethane acrylate is soft-chain water-based polyurethane acrylate. Through the UV curing effect, the surface of the coating is wrinkled, and the coating with the self-cleaning effect is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional coatings, and in particular to an anti-fouling self-cleaning coating with a micro-nano surface structure. Background Art

[0002] The self-cleaning coating can automatically remove surface pollutants or dust particles under the action of external forces such as gravity, rain, and wind, or remove them through photocatalytic degradation. It has the advantages of saving water, energy, and environmental protection. It has important application prospects in the construction, transportation, new energy and other industries. In recent years, it has become one of the research hotspots of advanced functional coatings. The antifouling performance of self-cleaning materials is mainly affected by two aspects. On the one hand, the coating surface is physically or chemically modified by using fluorine-containing or silicon-containing compounds with low surface energy. On the other hand, rough or smooth surface morphology is prepared, including superhydrophobic coatings and superamphiphobic coatings. Superhydrophobic coatings are a kind of functional biomimetic coatings prepared by imitating the hydrophobic properties of lotus leaves, cabbage, rose petals, etc. It can achieve a water contact angle (WCA) far greater than 150° and a water sliding angle (WSA) less than 10°. Water droplets can easily slide from the surface and take away pollutants, showing excellent self-cleaning properties. Studies have found that surface roughness and chemical composition play a key role in the realization of superhydrophobic materials. At present, researchers have prepared many superhydrophobic coatings based on the following two principles: (1) low surface energy substances modify rough surfaces; (2) increase the roughness of the hydrophobic coating surface. However, the antifouling effect of most superhydrophobic materials is relatively short-lived because the superhydrophobic state is a metastable interface state. During use, the super-hydrophobic surface can easily change from a non-wetting Cassie-Baxter state to a fully wetted Wenzel state. In addition, when the super-hydrophobic coating is subjected to degradation by low-surface-energy molecules, external force extrusion, mechanical vibration, etc., the durability of the coating surface will deteriorate, and the super-hydrophobic property will be lost. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a micro-nano surface structure anti-fouling self-cleaning coating, which is used to wrinkle the coating surface through UV curing to obtain a coating with a self-cleaning effect.

[0004] Technical solution: A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprises the following ingredients: Wherein, the waterborne polyurethane acrylate A is a hard-chain polyurethane acrylate; the photocatalytic degradation particles are coated with waterborne polyurethane acrylate B, which is a soft-chain waterborne polyurethane acrylate. Preferably, the preparation method of the waterborne polyurethane acrylate is: S11. isophorone diisocyanate, diol and dibutyltin dilaurate are stirred and mixed uniformly, and then nitrogen is introduced to react at 50-60° C. for 1-2 hours, wherein the initial molar ratio of -NCO and -OH functional groups is 2-4:1; S12. Dissolve 2,2-dihydroxymethylpropionic acid in N,N-dimethylformamide, add 1 to 2 drops of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 40 to 50 ° C for chain extension reaction for 1 to 2 hours, wherein the amount of 2,2-dihydroxymethylpropionic acid added to the entire system is 3 to 4 wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 45-55° C., a capping reaction is performed, and after cooling, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Preferably, the diol is polyethylene glycol. When the polyethylene glycol is selected from any one of polyethylene glycol 200, polyethylene glycol 300 or polyethylene glycol 400, a hard-chain waterborne polyurethane acrylate is obtained; when the polyethylene glycol is selected from any one of polyethylene glycol 1000, polyethylene glycol 2000, polyethylene glycol 4000 or polyethylene glycol 6000, a soft-chain waterborne polyurethane acrylate is obtained. Preferably, the preparation method of the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, and the dispersion is obtained after being uniformly dispersed by stirring. Ammonia water is added to the dispersion, and stirring is continued. Finally, tetrabutyl titanate is slowly added dropwise to react at a constant temperature to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined to obtain hollow mesoporous titanium dioxide; S22. Add soft chain waterborne polyurethane acrylate to water, stir and disperse evenly, immerse the hollow mesoporous titanium dioxide prepared in step S11 in the polyurethane acrylate solution, immerse under vacuum to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. The nano-titanium dioxide is added to an aqueous solution of sodium dodecyl sulfate, ultrasonically dispersed uniformly, potassium persulfate is added as an initiator, methyl methacrylate is added, and the reaction is heated to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Preferably, the concentration of PS microspheres in the dispersion in S21 is 0.1-0.2 mg / mL, the concentration of hexadecyltrimethylammonium bromide is 0.3-0.4 mg / mL, the concentration of ammonia water is 1-2 vt%, and the concentration of tetrabutyl titanate is 0.5-1 vt%. Preferably, the temperature of the isothermal reaction in S21 is 50-60° C., the time is 1-2 h, the calcination temperature is 500-550° C., and the calcination time is 2-3 h. Preferably, the immersion time in S22 is 10-20 min, and the vacuum degree is -0.2 to -0.1 MPa. Preferably, the mass ratio of the S23 methyl methacrylate to nano titanium dioxide is 10:1-2, the heating reaction temperature is 70-80°C, and the time is 10-15 hours. The preparation method of the above-mentioned micro-nano surface structure anti-fouling self-cleaning coating comprises the following steps: firstly adding the water-based polyurethane acrylate into water, stirring and mixing evenly, then sequentially adding photocatalytic degradation particles, dispersant, defoaming agent, UV photoinitiator and adhesion promoter, stirring evenly to obtain the micro-nano surface structure anti-fouling self-cleaning coating. Beneficial effects: The anti-fouling self-cleaning coating with micro-nano surface structure of the present invention has the following advantages: 1. In the present invention, titanium dioxide particles with a hollow mesoporous structure are first prepared, and polyurethane acrylate containing more soft chains is adsorbed by titanium dioxide particles, and microspheres are coated with photodegradable polymethacrylate, and the coating layer of polymethacrylate contains nano titanium dioxide. During the ultraviolet curing process, titanium dioxide can catalyze the faster degradation of polymethacrylate, so that the polyurethane acrylate containing more soft chains coated in the titanium dioxide particles can flow out, and the entire coating also contains polyurethane acrylate containing less soft chains. The outer layer of polyurethane acrylate containing less soft chains is cured first, and the polyurethane acrylate containing more soft chains is cured later. The polyurethane acrylate containing less soft chains on the surface is cured first and shrinks without restriction. Then, when the polyurethane acrylate containing more soft chains on the surface layer is cured later, its shrinkage will be constrained by the adhesion between the coating and the substrate, and the cohesive force caused by the tension of the inner layer acts on the already shrunk upper layer, resulting in compression of the upper layer, and finally wrinkles of micro-nano structure are generated on the surface layer, so as to obtain a coating with a micro-nano surface structure; 2. The present invention uses two titanium dioxides of different particle sizes to further enhance the micro-nano effect on the coating surface. When polymethacrylate degrades, the nano-titanium dioxide in the polymethacrylate film is exposed, and the coating contains both micron-sized titanium dioxide and nano-sized titanium dioxide, ultimately obtaining a coating with a micro-nano surface structure. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 The preparation method of water-based soft-chain polyurethane acrylate is as follows: S11. isophorone diisocyanate, polyethylene glycol 1000 and dibutyltin dilaurate were stirred and mixed uniformly, and then nitrogen was introduced to react at 50° C. for 2 h, wherein the initial molar ratio of -NCO and -OH functional groups was 2:1; S12. Dissolve 2,2-dihydroxymethylpropionic acid in N,N-dimethylformamide, add 1 drop of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 40°C for chain extension reaction for 2h, wherein the amount of 2,2-dihydroxymethylpropionic acid added to the whole system is 3wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 55° C., a capping reaction is performed, and after the temperature is lowered, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Example 2 The preparation method of water-based soft-chain polyurethane acrylate is as follows: S11. isophorone diisocyanate, polyethylene glycol 2000 and dibutyltin dilaurate were stirred and mixed uniformly, and then nitrogen was introduced to react at 60° C. for 1 h, wherein the initial molar ratio of -NCO and -OH functional groups was 3:1; S12. Dissolve 2,2-dihydroxymethylpropionic acid in N,N-dimethylformamide, add 1 drop of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 40°C for chain extension reaction for 2h, wherein the amount of 2,2-dihydroxymethylpropionic acid added to the whole system is 3wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 55° C., a capping reaction is performed, and after the temperature is lowered, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Example 3 The preparation method of water-based soft-chain polyurethane acrylate is as follows: S11. isophorone diisocyanate, polyethylene glycol 4000 and dibutyltin dilaurate were stirred and mixed uniformly, and then nitrogen was introduced to react at 55° C. for 1.5 h, wherein the initial molar ratio of -NCO and -OH functional groups was 2:1; S12. Dissolve 2,2-dihydroxymethylpropionic acid in N,N-dimethylformamide, add 2 drops of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 50°C for chain extension reaction for 2h, wherein the amount of 2,2-dihydroxymethylpropionic acid added to the entire system is 3.5wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 45° C., a capping reaction is performed, and after the temperature is lowered, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Example 4 The preparation method of water-based soft-chain polyurethane acrylate is as follows: S11. isophorone diisocyanate, polyethylene glycol 6000 and dibutyltin dilaurate were stirred and mixed uniformly, and then nitrogen was introduced to react at 50° C. for 1.5 h, wherein the initial molar ratio of -NCO and -OH functional groups was 4:1; S12. Dissolve 2,2-dimethylolpropionic acid in N,N-dimethylformamide, add 1 drop of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 40°C for chain extension reaction for 2h, wherein the amount of 2,2-dimethylolpropionic acid added to the whole system is 3.6wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 50° C., a capping reaction is performed, and after the temperature is lowered, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Example 5 The preparation method of water-based hard-chain polyurethane acrylate is as follows: S11. isophorone diisocyanate, polyethylene glycol 200 and dibutyltin dilaurate were stirred and mixed uniformly, and then nitrogen was introduced to react at 55° C. for 1 h, wherein the initial molar ratio of -NCO and -OH functional groups was 2:1; S12. Dissolve 2,2-dihydroxymethylpropionic acid in N,N-dimethylformamide, add 1 drop of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 45°C for chain extension reaction for 1.5h, wherein the amount of 2,2-dihydroxymethylpropionic acid added to the whole system is 3wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 55° C., a capping reaction is performed, and after the temperature is lowered, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Example 6 The preparation method of water-based hard-chain polyurethane acrylate is as follows: S11. isophorone diisocyanate, polyethylene glycol 300 and dibutyltin dilaurate were stirred and mixed uniformly, and then nitrogen was introduced to react at 50° C. for 1 h, wherein the initial molar ratio of -NCO and -OH functional groups was 3:1; S12. Dissolve 2,2-dimethylolpropionic acid in N,N-dimethylformamide, add 1 drop of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, and heat to 45°C for chain extension reaction for 1:h, wherein the amount of 2,2-dimethylolpropionic acid added to the whole system is 4wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 55° C., a capping reaction is performed, and after the temperature is lowered, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Example 7 The preparation method of water-based hard-chain polyurethane acrylate is as follows: S11. isophorone diisocyanate, polyethylene glycol 400 and dibutyltin dilaurate were stirred and mixed uniformly, and then nitrogen was introduced to react at 55° C. for 1.5 h, wherein the initial molar ratio of -NCO and -OH functional groups was 2:1; S12. Dissolve 2,2-dihydroxymethylpropionic acid in N,N-dimethylformamide, add 1 drop of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 45°C for chain extension reaction for 1.5h, wherein the amount of 2,2-dihydroxymethylpropionic acid added to the whole system is 3wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 45° C., a capping reaction is performed, and after the temperature is lowered, TEA is added for neutralization to obtain waterborne polyurethane acrylate. Example 8 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.3 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.1 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 1 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 0.5 vt%. The reaction is carried out at a constant temperature of 60°C for 2 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 550°C for 2 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 1 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under vacuum for 10 min at a vacuum degree of -0.1 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. Add nano-titanium dioxide to an aqueous solution of sodium dodecyl sulfate, disperse it evenly by ultrasonication, add potassium persulfate as an initiator, add methyl methacrylate, the mass ratio of methyl methacrylate to nano-titanium dioxide is 10:1, and heat the reaction at 70°C for 15h to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Example 9 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.4 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.2 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 2 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 1 vt%. The mixture is reacted at a constant temperature of 50°C for 1 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 500°C for 3 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 2 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under a vacuum environment for 20 minutes at a vacuum degree of -0.1 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. Add nano-titanium dioxide to an aqueous solution of sodium dodecyl sulfate, disperse it evenly by ultrasonication, add potassium persulfate as an initiator, add methyl methacrylate, the mass ratio of methyl methacrylate to nano-titanium dioxide is 10:2, and heat the reaction at 80°C for 10h to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Example 10 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.35 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.12 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 1.4 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 0.9 vt%. The mixture is reacted at a constant temperature of 55°C for 2 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 500°C for 2 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 3 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under a vacuum environment for 10 min, and the vacuum degree is -0.1 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. Add nano-titanium dioxide to an aqueous solution of sodium dodecyl sulfate, disperse it evenly by ultrasonication, add potassium persulfate as an initiator, add methyl methacrylate, the mass ratio of methyl methacrylate to nano-titanium dioxide is 10:1.4, and heat the reaction at 70°C for 14h to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Embodiment 11 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.38 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.16 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 1.5 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 0.8 vt%. The reaction is carried out at a constant temperature of 55°C for 1 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 550°C for 3 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 1 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under a vacuum environment for 20 min at a vacuum degree of -0.2 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. Add nano-titanium dioxide to an aqueous solution of sodium dodecyl sulfate, disperse it evenly by ultrasonication, add potassium persulfate as an initiator, add methyl methacrylate, the mass ratio of methyl methacrylate to nano-titanium dioxide is 10:1.6, and heat the reaction at 75°C for 12h to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Comparative Example 1 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.38 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.16 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 1.5 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 0.8 vt%. The reaction is carried out at a constant temperature of 55°C for 1 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 550°C for 3 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 1 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under a vacuum environment for 20 min at a vacuum degree of -0.2 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. Add nano-titanium dioxide to an aqueous solution of sodium dodecyl sulfate, disperse it evenly by ultrasonication, add potassium persulfate as an initiator, add methyl methacrylate, the mass ratio of methyl methacrylate to nano-titanium dioxide is 10:1.6, and heat the reaction at 75°C for 12h to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Comparative Example 2 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.38 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.16 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 1.5 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 0.8 vt%. The reaction is carried out at a constant temperature of 55°C for 1 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 550°C for 3 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 1 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under a vacuum environment for 20 min at a vacuum degree of -0.2 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. After adding potassium persulfate to water, methyl methacrylate was added and the reaction was heated at 75° C. for 12 h to obtain a polymethacrylate solution; S24. Adding the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Comparative Example 3 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.38 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.16 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 1.5 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 0.8 vt%. The reaction is carried out at a constant temperature of 55°C for 1 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 550°C for 3 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 1 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under a vacuum environment for 20 min at a vacuum degree of -0.2 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. Add nano-titanium dioxide to an aqueous solution of sodium dodecyl sulfate, disperse it evenly by ultrasonication, add potassium persulfate as an initiator, add methyl methacrylate, the mass ratio of methyl methacrylate to nano-titanium dioxide is 10:1.6, and heat the reaction at 75°C for 12h to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. Comparative Example 4 A micro-nano surface structure anti-fouling self-cleaning coating, the coating comprising the following ingredients: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, the concentration of which is 0.38 mg / mL, and the dispersion is uniformly dispersed by stirring to obtain a dispersion having a concentration of 0.16 mg / mL. Ammonia water is added to the dispersion, and the volume concentration of ammonia water in the reaction system is 1.5 vt%. The stirring is continued, and finally, tetrabutyl titanate is slowly added dropwise, and the volume concentration of tetrabutyl titanate in the reaction system is 0.8 vt%. The reaction is carried out at a constant temperature of 55°C for 1 h to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined at a temperature of 550°C for 3 h to obtain hollow mesoporous titanium dioxide; S22. The soft-chain water-based polyurethane acrylate prepared in Example 1 is added to water, stirred and dispersed evenly, and the hollow mesoporous titanium dioxide prepared in step S11 is immersed in the polyurethane acrylate solution under a vacuum environment for 20 min at a vacuum degree of -0.2 MPa to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. Add nano-titanium dioxide to an aqueous solution of sodium dodecyl sulfate, disperse it evenly by ultrasonication, add potassium persulfate as an initiator, add methyl methacrylate, the mass ratio of methyl methacrylate to nano-titanium dioxide is 10:1.6, and heat the reaction at 75°C for 12h to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles. The micro-nano surface structure anti-fouling self-cleaning coating prepared in the above examples and comparative examples was applied to the substrate at a coating amount of 15 g / m 2 , the number of coating passes is unlimited; finally, the coating composition is cured by ultraviolet irradiation, and the adhesion (coating adhesion: measured according to ASTM D3359-09) and other test properties are tested as shown in the following table. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A micro-nano surface structure anti-fouling self-cleaning coating, characterized in that: The coating comprises the following ingredients: Wherein, the waterborne polyurethane acrylate A is a hard-chain polyurethane acrylate; the photocatalytic degradation particles are coated with waterborne polyurethane acrylate B, which is a soft-chain waterborne polyurethane acrylate.

2. The anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 1, characterized in that: The preparation method of the waterborne polyurethane acrylate is: S11. isophorone diisocyanate, diol and dibutyltin dilaurate are stirred and mixed uniformly, and then nitrogen is introduced to react at 50-60° C. for 1-2 hours, wherein the initial molar ratio of -NCO and -OH functional groups is 2-4:1; S12. Dissolve 2,2-dihydroxymethylpropionic acid in N,N-dimethylformamide, add 1 to 2 drops of dibutyltin dilaurate, control the dripping rate and drip into the system of step S1, raise the temperature to 40 to 50 ° C for chain extension reaction for 1 to 2 hours, wherein the amount of 2,2-dihydroxymethylpropionic acid added to the entire system is 3 to 4 wt%; S13. Hydroquinone and β-hydroxyethyl methacrylate are added dropwise to the reaction system, the temperature is raised to 45-55° C., a capping reaction is performed, and after cooling, TEA is added for neutralization to obtain waterborne polyurethane acrylate.

3. The anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 2, characterized in that: The diol is polyethylene glycol, and when the polyethylene glycol is selected from any one of polyethylene glycol 200, polyethylene glycol 300 or polyethylene glycol 400, a hard-chain waterborne polyurethane acrylate is obtained; When the polyethylene glycol is selected from any one of polyethylene glycol 1000, polyethylene glycol 2000, polyethylene glycol 4000 or polyethylene glycol 6000, a soft-chain waterborne polyurethane acrylate is obtained.

4. The anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 3, characterized in that: The method for preparing the photocatalytic degradation particles comprises the following steps: S21. The PS microspheres are dispersed in an ethanol aqueous solution containing hexadecyltrimethylammonium bromide, and the dispersion is obtained after being uniformly dispersed by stirring. Ammonia water is added to the dispersion, and stirring is continued. Finally, tetrabutyl titanate is slowly added dropwise to react at a constant temperature to obtain a titanium dioxide precursor, and the titanium dioxide precursor is calcined to obtain hollow mesoporous titanium dioxide; S22. Add soft chain waterborne polyurethane acrylate to water, stir and disperse evenly, immerse the hollow mesoporous titanium dioxide prepared in step S11 in the polyurethane acrylate solution, immerse under vacuum to obtain titanium dioxide particles adsorbing polyurethane acrylate; S23. The nano-titanium dioxide is added to an aqueous solution of sodium dodecyl sulfate, ultrasonically dispersed uniformly, potassium persulfate is added as an initiator, methyl methacrylate is added, and the reaction is heated to obtain a polymethacrylate solution containing nano-titanium dioxide; S24. Add the titanium dioxide particles adsorbing polyurethane acrylate prepared in step S22 to the polymethacrylate solution containing nano titanium dioxide prepared in step S23, so that the surface of the titanium dioxide particles adsorbing polyurethane acrylate is coated with polymethacrylate to obtain photocatalytic degradation particles.

5. The anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 1, characterized in that: The concentration of PS microspheres in the dispersion of S21 is 0.1-0.2 mg / mL, the concentration of hexadecyltrimethylammonium bromide is 0.3-0.4 mg / mL, the concentration of ammonia water is 1-2 vt%, and the concentration of tetrabutyl titanate is 0.5-1 vt%.

6. The anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 1, characterized in that: The isothermal reaction temperature in S21 is 50-60° C., the time is 1-2 hours, the calcination temperature is 500-550° C., and the calcination time is 2-3 hours.

7. The anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 1, characterized in that: The immersion time in S22 is 10-20 minutes, and the vacuum degree is -0.2 to -0.1 MPa.

8. The anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 1, characterized in that: The mass ratio of the S23 methyl methacrylate to the nano titanium dioxide is 10:1-2, the heating reaction temperature is 70-80° C., and the reaction time is 10-15 hours.

9. The method for preparing the anti-fouling self-cleaning coating with a micro-nano surface structure according to claim 1, characterized in that: The following steps are involved: First, the waterborne polyurethane acrylate is added to water, and after stirring and mixing evenly, photocatalytic degradation particles, dispersant, defoamer, UV photoinitiator and adhesion promoter are added in sequence, and stirred evenly to obtain a micro-nano surface structure anti-fouling self-cleaning coating.

Citation Information

Patent Citations

  • Titanium-dioxide-based double-layer hollow material, preparation method thereof, and application thereof in photocatalytic treatment of hydrogen sulfide

    CN106732818A

  • Modified photo-curable waterborne polyurethane acrylate and preparation method and application thereof

    CN110157324A

  • Multifunctional Cu-TiO2-PU having both photocatalyst and adsorbent activity and manufacturing method thereof

    KR1020160121852A